Formen des Reisbaus in Nepal - Haffner, Willibald; Justus Liebig University Giessen (My University, 1973)
Die Untersuchung zeigt die dominierende Rolle des Reisbaus als Ordnungs- und Gestaltungsfaktor für die Kulturlandschaft Nepal. Die verschiedenen Formen des Reisbaus werden sowohl in ihrer ökologischen wie ethno-sozialen Bedingtheit gezeigt.

The study shows the dominant role of rice cultivation as a planning and design factor in the cultural landscape of Nepal. The different forms of rice cultivation are shown in their ecological as well as in their ethnological and social context.
Forms of rice cultivation in Nepal
Keywords: ddc:630